2011
DOI: 10.2174/157489211796957766
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Rafts and Fas/CD95 Signaling in Cancer Chemotherapy

Abstract: Cholesterol- and sphingolipid-rich membrane domains, termed lipid rafts, have been recently involved in the triggering of death receptor-mediated apoptosis. The alkyl-lysophospholipid analogue edelfosine was the first antitumor drug reported to induce apoptosis in cancer cells through co-clustering of lipid rafts and Fas/CD95 death receptor. Recruitment and aggregation of Fas/CD95 in lipid raft clusters was independent of its cognate ligand FasL/CD95L, and could be pharmacologically modulated. The adaptor mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 103 publications
(201 reference statements)
0
38
0
3
Order By: Relevance
“…Kruskal-Wallis P = 0.089 into lipid rafts (24). Addition of Ohmline for 24 hours at 1 mmol/L had no effect on SK3 or Orai1 protein expression, but totally delocalized SK3 and Orai1 channels from lipid-raft fractions ( Fig.…”
Section: Sk3 Action Is Mediated Through Its Association With the Oraimentioning
confidence: 84%
“…Kruskal-Wallis P = 0.089 into lipid rafts (24). Addition of Ohmline for 24 hours at 1 mmol/L had no effect on SK3 or Orai1 protein expression, but totally delocalized SK3 and Orai1 channels from lipid-raft fractions ( Fig.…”
Section: Sk3 Action Is Mediated Through Its Association With the Oraimentioning
confidence: 84%
“…Recent studies suggest that ET mainly accumulates in membrane lipid rafts and triggers the extrinsic apoptotic pathway throughout Fas/CD95 death receptor [9,10,23,27]. However, this mechanism might be diminished in the case of encapsulated drug, as it could be directed to different cell targets once inside the cell, promoting other drug actions and therefore overcoming resistance to the drug.…”
Section: 4mentioning
confidence: 99%
“…Lipid raft clustering has been found to be involved in apoptosis induction through the activation of caspase-8 probably due to causing Fas aggregation. 19 Lipid rafts and the distribution of Fas were determined in NB4 cells after treatment with A3D8 at 2.5 μg/ml for 3 days using a confocal microscopy. Lipid rafts were assessed by lipid raft marker FITC-Ctx B according to the reported method.…”
Section: Resultsmentioning
confidence: 99%
“…17 Lipid raft clustering has been found to be essential for apoptosis induction by several agents, which involves the recruitment of Fas, Fas-associated death domain (FADD) and caspase-8. 18,19 Recently it has been found that CD44 is a down-stream target of fusion protein AML1-ETO formed due to t(8;21) translocation in AML cells. 20 AML cells with this fusion protein should be more effective than other types of leukemia cells to A3D8-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%